P3-S1.27 Is antimicrobial resistance in Chlamydia trachomatis a reality?. (10th July 2011) - Pitt, R; Alexander, S; Horner, P; Ison, C
Abstract : Introduction: The use of single dose therapy and the emergence of a stable tetracycline resistant strain of Chlamydia suis has raised concerns regarding potential development of antimicrobial resistance (AMR) in C trachomatis (CT). Specimens sourced from patients with persistently confirmed CT infections after treatment with first line recommended therapies were examined for the presence of AMR determinants identified in other organisms. Methods: CT DNA positive specimens were examined for viable bacteria by tissue culture. Sequencing for mutations in three genes known to be involved in azithromycin (AZM) AMR; rplV, rplD and 23S rRNA (two alleles) and for the presence of six tetracycline AMR determinants; tet(A), tet(B), tet(C), tet(D), tet(E) and tet(M) was done. Susceptibility testing was performed using isolates grown in duplicate serial dilutions of AZM followed by quantitative RT-PCR. Isolates with a log or more increase in plasmid copy number were deemed resistant and those with a static or decreased copy number were deemed sensitive. Isolates were also screened for contaminating bacteria. Results: Nine isolates were retrieved from twenty CT NAAT positive patients. When examined by AZM MIC assays, all isolates were sensitive. An identical non-silent single nucleotide polymorphism (SNP) was identified in three clinical specimens and one isolate from three patients in the rplD gene. A non-silent SNP was also identified in the rplV gene in one of these patients. The pre and post treatment specimen from a further patient showed a non-silent SNP in the rplD gene and identical point mutations in both alleles of the 23S rRNA gene. The tet(M) resistance determinant was identified in ten specimens and five isolates from eleven different patients. All screens for contaminating bacteria were negative. Conclusions: Previously unreported mutations in genes responsible for AZM AMR in other organisms have been identified however all isolates were found to be AZM sensitive. Whilst the SNPs identified may not be significant, detection of them demonstrates that CT has undergone mutation in these key genes. A fragment of the tetracycline AMR determinant, tet(M) (responsible for high level tetracycline AMR in Neisseria gonorrhoeae ), was identified in several clinical specimens and in five isolates. The function of the tet(M) fragment in CT is currently unknown and the establishment of tetracycline MIC assays are a priority.